1989
DOI: 10.1073/pnas.86.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Identical structural changes in inherited albumin variants from different populations.

Abstract: Alloalbuminemia is rare and has a cumulative frequency of only 1 in 3000 in Europeans and Japanese. also occur in Japan. These results provide evidence for independent mutations at single sites in the albumin genome. The clustering of these and of several other amino acid exchanges in certain regions of the albumin molecule suggests two possibilities: that certain sites are hypermutable or that mutants involving certain sites are more subject to selection than mutants involving others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…In the present work the five variants were compared at pH 4.0 and 5.6 with reference alloalbumins for which the substitution was known. The reference variants with known substitutions are albumin Mexico (slow + 1, 550 Asp Gly) (10), albumin B Lubeck (slow +2, 570 Glu -* Lys) (15), and proalbumin Pollibauer (Lille type, slow +2, -2 Arg -+ His) (11). The five Japanese variants showed different combinations of mobilities in the two buffer systems; all were also different from albumin B and proallbumin Pollibauer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present work the five variants were compared at pH 4.0 and 5.6 with reference alloalbumins for which the substitution was known. The reference variants with known substitutions are albumin Mexico (slow + 1, 550 Asp Gly) (10), albumin B Lubeck (slow +2, 570 Glu -* Lys) (15), and proalbumin Pollibauer (Lille type, slow +2, -2 Arg -+ His) (11). The five Japanese variants showed different combinations of mobilities in the two buffer systems; all were also different from albumin B and proallbumin Pollibauer.…”
Section: Resultsmentioning
confidence: 99%
“…However, we recently reported that the 570 Glu -* Lys exchange is present in an albumin variant occurring in two unrelated Japanese and one Cambodian (15). The two type B albumins from Japan were designated Tokyo-1 and Shinanomachi-1, and the one from Cambodia was designated Phnom Penh.…”
Section: Sugita Et Al (21) Had Reported That the Molecular Abnormalitymentioning
confidence: 99%
See 3 more Smart Citations